Religious and Moral Attitudes of Catholics from Generation Z - Grzegorz Polok; Adam R. Szromek (Religions, 2023)
This paper discusses findings of studies concerning religious attitudes of Polish Catholics belonging to the so-called Generation Z, i.e., people born during the digital revolution. The authors present religious attitudes of Generation Z representatives against the background of other European states relating to religious practices and opinions concerning the acceptability of abortion, euthanasia, divorce, contraceptives and other conduct not consistent with the Catholic Church teachings. The findings prove that even though the Polish society, including those of Generation Z, is distinguishable from European countries with its high percentage of people engaging in religious practices, the observed trends and the dominance of attitudes contrary to the teachings of the Catholic Church indicate the possibility of maintaining a downward trend in the number of Catholics in Poland.